The Challenges of Malaysian Dry Ports Development - Jagan Jeevan; Shu-ling Chen; Eon-seong Lee (Asian Journal of Shipping and Logistics, 2015)
This paper examines the functions and challenges of dry ports development in Malaysia through 11 face-to-face interviews with dry port stakeholders. The findings reveal that Malaysian dry ports are developed to accelerate national and international business, to activate intermodalism in the nation, to promote regional economic development and to enhance seaport competitiveness. Malaysian dry ports perform the function of transport and logistics, information processing, seaports and value-added services. Challenges facing Malaysian dry ports include insufficient railway tracks, unorganized container planning on the rail deck, highly dependent on single mode of transportation, poor recognition from the seaport community, and competition from localized seaports. This paper further indicates strategies for coping with these challenges and identifies future opportunities for Malaysian dry ports development.